2020
DOI: 10.1016/j.chest.2019.11.046
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Digital vs Analog Drainage for Air Leak After Surgical Resection or Spontaneous Pneumothorax

Abstract: Word Count: 252 Manuscript Word Count (excluding references): 2376 Conflict of Interest: All authors have no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For chest tube removal, we mainly judged the removal threshold by direct inspection of air bubbles in the water-seal chamber and recorded drainage volume based on traditional drainage system. Additionally, the digital chest drainage, a newly chest drainage system, could be used to guide chest tube removal ( 29 ). Digital drainage system was applied only in a few regions with high healthcare expenditure, while traditional drainage system was more widely used ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…For chest tube removal, we mainly judged the removal threshold by direct inspection of air bubbles in the water-seal chamber and recorded drainage volume based on traditional drainage system. Additionally, the digital chest drainage, a newly chest drainage system, could be used to guide chest tube removal ( 29 ). Digital drainage system was applied only in a few regions with high healthcare expenditure, while traditional drainage system was more widely used ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinically appropriate threshold flow of air leak flow for chest tube removal differs substantially across trials, but reported levels generally range from 0 to 50 mL/min over a period of 1-12 hours prior to removal (8,15). In this study, we utilized 20 mL/min as prompting consideration for chest tube removal.…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that a tube thoracostomy can be safely removed once an air leak is <20 mL/min (5). Utilization of a digital drainage device permits earlier removal of a pleural drain, which in turn decreases hospital length of stay (LOS) (6)(7)(8). These units will undoubtedly become more commonplace as affordability improves.…”
Section: Classification Of Severitymentioning
confidence: 99%
“…Duration refers to how long the leak has been present. Volume refers to the degree of leak, which can be assessed using an analog or digital collection system (6). Put simply, an air leak is less likely to spontaneously resolve if there is a large leak that has been present for a longer period of time and is getting worse (23).…”
Section: Treatmentmentioning
confidence: 99%